Effect of mupirocin treatment on nasal, pharyngeal, and perineal carriage of Staphylococcus aureus in healthy adults. - Wertheim, H; Verveer, J; Boelens, H; van Belkum, A; Verbrugh, H; Vos, M (2005)
Nasal carriage of Staphylococcus aureus is an important risk factor for S. aureus infections. Mupirocin nasal ointment is presently the treatment of choice for decolonizing the anterior nares. However, recent clinical trials show limited benefit from mupirocin prophylaxis in preventing nosocomial S. aureus infections, probably due to (re)colonization from extranasal carriage sites. Therefore, we studied the effectiveness of mupirocin nasal ointment treatment on the dynamics of S. aureus nasal and extranasal carriage. Twenty noncarriers, 26 intermittent carriers, and 16 persistent carriers had nasal, throat, and perineum samples taken 1 day before and 5 weeks after mupirocin treatment (twice daily for 5 days) and assessed for growth of S. aureus. The identities of cultured strains were assessed by restriction fragment length polymorphisms of the coagulase and protein A genes. The overall carriage rate (either nasal, pharyngeal, or perineal carrier or a combination) was significantly reduced after mupirocin treatment from 30 to 17 carriers (P = 0.003). Of the 17 carriers, 10 (60%) were still colonized with their old strain, 6 (35%) were colonized with an exogenous strain, and 1 (5%) was colonized with both. Two noncarriers became carriers after treatment. The acquisition of exogenous strains after mupirocin treatment is a common phenomenon. The finding warrants the use of mupirocin only in proven carriers for decolonization purposes. Mupirocin is effective overall in decolonizing nasal carriers but less effective in decolonizing extranasal sites.